In vivo investigation of polymer-ceramic PCL/HA and PCL/β-TCP 3D composite scaffolds and electrical stimulation for bone regeneration - Helaehil, Júlia Venturini (2022)
Critical bone defects are a major clinical challenge in reconstructive bone surgery. Polycaprolactone (PCL) mixed with bioceramics, such as hydroxyapatite (HA) and tricalcium phosphate (TCP), create composite scaffolds with improved biological recognition and bioactivity. Electrical stimulation (ES) aims to compensate the compromised endogenous electrical signals and to stimulate cell proliferation and differentiation. We investigated the effects of composite scaffolds (PCL with HA; and PCL with β-TCP) and the use of ES on critical bone defects in Wistar rats using eight experimental groups: untreated, ES, PCL, PCL/ES, HA, HA/ES, TCP, and TCP/ES. The investigation was based on histomorphometry, immunohistochemistry, and gene expression analysis. The vascular area was greater in the HA/ES group on days 30 and 60. Tissue mineralization was greater in the HA, HA/ES, and TCP groups at day 30, and TCP/ES at day 60. Bmp-2 gene expression was higher in the HA, TCP, and TCP/ES groups at day 30, and in the TCP/ES and PCL/ES groups at day 60. Runx-2, Osterix, and Osteopontin gene expression were also higher in the TCP/ES group at day 60. These results suggest that scaffolds printed with PCL and TCP, when paired with electrical therapy application, improve bone regeneration.